2003
DOI: 10.1124/jpet.102.044271
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cytochrome P4501B1 in Benzo[a]pyrene Bioactivation to DNA-Binding Metabolites in Mouse Vascular Smooth Muscle Cells: Evidence from32P-Postlabeling for Formation of 3-Hydroxybenzo[a]pyrene and Benzo[a]pyrene-3,6-quinone as Major Proximate Genotoxic Intermediates

Abstract: Benzo [a]pyrene (BP), a polycylic aromatic hydrocarbon (PAH), is a potent atherogen and carcinogen in laboratory animals. Since genotoxic mechanisms may contribute to the development of atherosclerosis by PAHs, we have tested the hypotheses that: 1) BP induces DNA adducts in mouse aortic smooth muscle cells (SMCs); 2) 3-hydroxybenzo[a]pyrene (3-OH-BP) and benzo [a]pyrene-3,6-quinone (BPQ) are proximate genotoxic metabolites; and 3) cytochrome P4501B1 (CYP1B1) mediates the activation of BP and its metabolites t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…In particular, it has been hypothesized that AhR ligands disrupt the endothelial cell wall integrity and permeability, which allows more uptake of cholesterol-rich lipoprotein and influx of inflammatory cells, such as T lymphocyte, into the plaque (Curfs et al, 2005), resulting in atheroma formation and ischemic heart diseases (Lee et al, 2003). This hypothesis has been supported by several studies that showed that DNA and protein adduct formation in atherosclerotic lesions in rats and mice SMCs pretreated with 3MC or BaP, or exposed to cigarette smoke, were significantly inhibited by the antioxidant, N-acetylcysteine (NAC), suggesting a direct link between ROS production and atherogenesis (De Flora et al, 1996;Izzotti et al, 1994;Izzotti et al, 1995;Izzotti et al, 1998;Moorthy et al, 2002;Moorthy et al, 2003). Furthermore, the ability of TCDD to induce ROS production and increase DNA degradation in Medaka fish embryonic heart and veins of the embryonic vasculature was partially inhibited by NAC and completely abolished with PBO treatment (Cantrell et al, 1996).…”
Section: Oxidative Stress and Dna Adduct Formationmentioning
confidence: 85%
See 3 more Smart Citations
“…In particular, it has been hypothesized that AhR ligands disrupt the endothelial cell wall integrity and permeability, which allows more uptake of cholesterol-rich lipoprotein and influx of inflammatory cells, such as T lymphocyte, into the plaque (Curfs et al, 2005), resulting in atheroma formation and ischemic heart diseases (Lee et al, 2003). This hypothesis has been supported by several studies that showed that DNA and protein adduct formation in atherosclerotic lesions in rats and mice SMCs pretreated with 3MC or BaP, or exposed to cigarette smoke, were significantly inhibited by the antioxidant, N-acetylcysteine (NAC), suggesting a direct link between ROS production and atherogenesis (De Flora et al, 1996;Izzotti et al, 1994;Izzotti et al, 1995;Izzotti et al, 1998;Moorthy et al, 2002;Moorthy et al, 2003). Furthermore, the ability of TCDD to induce ROS production and increase DNA degradation in Medaka fish embryonic heart and veins of the embryonic vasculature was partially inhibited by NAC and completely abolished with PBO treatment (Cantrell et al, 1996).…”
Section: Oxidative Stress and Dna Adduct Formationmentioning
confidence: 85%
“…Oxidative stress and DNA adduct formation have been implicated in the pathogenesis and progression of several CVDs, in which they represent an initiator key of gene mutations and thus organ dysfunction and carcinogenesis (Dhalla et al, 2000;Moorthy et al, 2003;Morganti et al, 2002;Ross et al, 2001). Although it is not clear how oxidative stress causes cardiac dysfunction, several mechanisms have been postulated (Dhalla et al, 2000).…”
Section: Oxidative Stress and Dna Adduct Formationmentioning
confidence: 95%
See 2 more Smart Citations
“…Some studies evaluated the in vitro 3-OH-BaP effects and showed that low concentrations of 3-OH-BaP (from 8 to 67 ng mL À1 ) may exert estrogenic activity (van Lipzig et al 2005) and form covalent bonds with macromolecules (Moorthy et al 2003;Sugihara and James 2003), leading to adverse consequences at the organism level. Although adverse effects were not assessed and the levels of free 3-OH-BaP measured in plasma (0.4 ng mL À1 ) were lower than concentrations capable of producing toxic effects, as it was quantified in one pooled sample, the levels obtained in our study may have been diluted.…”
Section: Discussionmentioning
confidence: 99%